Synergistic action of chemical compounds and spirulina extracts (One Health & Risk Management, 2024)
Introduction. Antimicrobial resistance is a critical global issue, and the demand for new drugs is urgent. The current model of antimicrobial discovery is not providing sufficient new agents to address current levels of antimicrobial resistance. In this study, we aim to assess the antimicrobial activity of recently synthesized chemical compounds and spirulina extracts, along with their associative effects.Material and methods. It is an experimental study, which includes seven newly synthesized chemical compounds and three extracts from Spirulina platensis.Results. The in vitro results of the present study determined the MIC values of chemical compounds and spirulina extracts against gram-negative, gram-positive microorganisms, and fungi of the genus Candida. The optimal combination of two compounds can enhance benefits over time and minimize side effects. The synergistic or partially synergistic effects of biological compounds in conjunction with chemical compounds strongly corroborated this assertion. Time-kill curves and FICI scores confirmed the ability of the compounds to synergistically reduce the microbial count below the lowest detectable limit within 24 hours.Conclusions. Our study offers a potential therapeutic option for antibiotic-resistant microbial agents by combining natural extracts with a variety of chemical compounds from different classes. The results of the present study are promising, and this knowledge holds potential utility for the development of future therapeutic strategies.